Complete Recovery of Oxysterol 7α-Hydroxylase Deficiency by Living Donor Transplantation in a 4-Month-Old Infant: the First Korean Case Report and Literature Review - Hong, Jeana; Oh, Seak Hee; Yoo, Han-Wook; Nittono, Hiroshi; Kimura, Akihiko; Kim, Kyung Mo (Journal of Korean medical science, 2018)
Oxysterol 7α-hydroxylase deficiency is a very rare liver disease categorized as inborn errors of bile acid synthesis, caused by mutations. As it may cause rapid progression to end-stage liver disease even in early infancy, a high index of suspicion is required to prevent fatal outcomes. We describe the case of a 3-month-old boy with progressive cholestatic hepatitis and severe hepatic fibrosis. After excluding other etiologies for his early liver failure, we found that he had profuse urinary excretion of 3β-monohydroxy-Δ -bile acid derivatives by gas chromatography/mass spectrometry analysis with dried urine spots on filter paper. He was confirmed to have a compound heterozygous mutation (p.Arg388Ter and p.Tyr469IlefsX5) of the gene. After undergoing liver transplantation (LT) from his mother at 4 months of age, his deteriorated liver function completely normalized, and he had normal growth and development until the current follow-up at 33 months of age. We report the first Korean case of oxysterol 7α-hydroxylase deficiency in the youngest infant reported to undergo successful living donor LT to date.